Effects of Kamishoyosan, a Traditional Japanese Kampo Medicine, on Pain Conditions in Patients with Intractable Persistent Dentoalveolar Pain Disorder. (1st October 2015) - Arai, Young-Chang P.; Makino, Izumi; Aono, Shuichi; Yasui, Hiromichi; Isai, Hideya; Nishihara, Makoto; Hatakeyama, Noboru; Kawai, Takashi; Ikemoto, Tatsunori; Inoue, Shinsuke; Ushida, Takahiro
Abstract : There are patients who suffer from persistent dentoalveolar pain disorder (PDAP) which is a pain of the teeth, either dentoalveolar pain or nonodontogenic toothache, and its cause has not yet been identified. An effective intervention for PDAP has not yet been established. Interventions for patients with PDAP are generally pharmacological treatments such as antidepressants, anticonvulsants, and pregabalin. However, these medicines are not always effective for patients. The pain disorder in the orofacial region including temporomandibular disorder (TMD) and PDAP was effectively treated with our original exercise therapy. However, we did observe some intractable cases of PDAP even when our original exercise therapy was used. This paper presents our findings in which Kamishoyosan improved the pain intensity in 14 out of 15 PDAP patients refractory to our original exercise therapy.